PENERAPAN MODEL DIRECT INSTRUCTION DENGAN MEDIA DAKON UNTUK MENINGKATKAN HASIL BELAJARA MATEMATIKA MATERI PERKALIAN SISWA KELAS II SD NEGERI 2 TAMANWINANGUN TAHUN AJARAN 2015/2016 - kurniawan, asrul (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Direct Instruction Model Using Dakon Media in Improving Mathematics Learning about Multiplication for the Second Grade Students of SD Negeri 2Tamanwinangun in the Academic Year of 2015/2016. This researchis based on the low understanding of caoncept in multiplication by the evidence of the low learning outcomes of Mathematics. The objectives of this research areto improve Mathematic learningoutcomes about multiplication. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection.Subjects of the research were 25 students of the second grade of SD Negeri2 Taanwinangun. Source of data were derived from students, teacher, and document. Techniques of collecting data were observation, interview, and document. The conclusion of this research is the application of direct instruction model using dakon media can improve Mathematics learning about multiplication for the second grade students. It can be seen from the increase of learning outcomes.The result of learning outcomes before treatment is 48% then increase become 62.5% in the first cycle, decrease in the second cycle to 54.43%, and increase in the third cycle to 86.66%.Keywords: direct insrtuction, dakon media, multiplication, mathematics Abstrak: Penerapan Model Direct Instruction dengan Media Dakon untuk Meningkatkan Hasil Belajar Matematika Materi Perkalian Siswa Kelas II SD Negeri 2 Tamanwinangun Tahun Ajaran 2015/2016. Penelitian ini dilatar belakangi rendahnya pemahaman konsep perkalian yang dibuktukan rendahnya hasil belajar Matematika. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar matematika tentang materi perkalian. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif yang dilaksanakan dalam tiga siklus. Masing-masing siklus mencakup tahap perencanaan, tindakan, observasi dan refleksi. Subjek penelitian ini adalah siswa kelas II SD Negeri 2 Tamanwinangun yang berjumlah 25 siswa. Teknik pengumpulan data menggunakan tes, observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model direct instruction dapat meningkatkan hasil belajar siswa. Hal ini dibuktikan dengan persentase ketuntasan siswa. Pada siklus I menjadi 62,5%, pada siklus II turun menjadi 54,43%, dan pada siklus III kembali meningkat menjadi 86,66%.Kata Kunci: direct instruction, media dakon, perkalian, matematika